Implementasi CQI Meningkatkan Kepatuhan Keluarga Pasien Melakukan Cuci Tangan Menggunakan Booklet Digital di Ruang ICU: Studi Kasus (Journal of Telenursing (JOTING), 2025)
This study aims to improve the compliance of ICU patient families to wash their hands in 6 steps. The method used is a case study using the CQI IHI Model for the improvement of the PDSA approach through the promotion of a 6-step handwashing digital booklet using a QR barcode scan. The study results showed that in terms of handwashing compliance, 2 days before the intervention, data was obtained that 33.3% of families washed their hands before the patient and 22.2% after the patient (n = 9). On 4 days of intervention, data was obtained that 100 percent washed their hands before and 72.7% after the patient (n = 11), which showed a significant increase, especially before the patient. There was a considerable increase in knowledge, with the average score of patients before the intervention being 32.7, and after the intervention, it increased to 72.7. The conclusion is that education using digital booklets can improve patient families' knowledge and compliance in washing their hands. This is because the media used is more innovative and attractive and has sustainability for use by ICU nurses.  Keywords: Digital Booklet, CQI IHI Model, 6-Step Handwashing, Patient Family